Highly conformal fabrication of nanopatterns on non-planar surfaces. Issue 22 (19th May 2016) - Massiot, Inès; Trompoukis, Christos; Lodewijks, Kristof; Depauw, Valérie; Dmitriev, Alexandre
Abstract : Bottom-up large-scale nanopatterns are fabricated conformally onto highly non-planar substrates using colloidal lithography. Abstract : While the number of techniques for patterning materials at the nanoscale exponentially increases, only a handful of methods approach the conformal patterning of strongly non-planar surfaces. Here, using the direct surface self-assembly of colloids by electrostatics, we produce highly conformal bottom-up nanopatterns with a short-range order. We illustrate the potential of this approach by devising functional nanopatterns on highly non-planar substrates such as pyramid-textured silicon substrates and inherently rough polycrystalline films. We further produce functionalized polycrystalline thin-film silicon solar cells with enhanced optical performance. The perspective presented here to pattern essentially any surface at the nanoscale, in particular surfaces with high inherent roughness or with microscale features, opens new possibilities in a wide range of advanced technologies from affordable photovoltaics and optoelectronics to cellular engineering.